PERAN GURU KELAS DALAM PEMBENTUKAN KARAKTER MELALUI PEMBELAJARAN TEMATIK DI SEKOLAH DASAR (AL-IHTIRAFIAH: JURNAL ILMIAH PENDIDIKAN GURU MADRASAH IBTIDAIYAH, 2021)
This paper aims to examine the role of class teachers in character formation through a thematic learning process. The method used in this discussion is the library research. The library is one of the sources of reference in this discussion by examining various sources from books, magazines, journals, and others for the topics of the relevant discussion. The results of the discussion make it clear that the role of the class teacher in character formation through thematic learning in elementary schools must be implemented through the implementation of character education in all subjects. Namely through exemplary and habituation exemplified by the teacher himself. Promoting character values through thematic learning includes, among other things, inserting character values into the lesson plans and preparing media, methods, teaching materials and assessment sheets.. As supporting material, there are routine activities in the form of 15-minute lectures by the teacher in class every Friday.